A Study on the Art Market of Calligraphy and Painting in Jiangnan in Ming and Qing Dynasties—Take Qiu Ying 's "Qing Ming Shang He Tu "and Xu Yang 's "Gu Su Prosperity Tu "as an example (Journal of Global Arts Studies, 2024)
Background: During the Ming dynasty and Qing dynasty periods, the prosperity of the commodity economy promoted the gradual commercialization of calligraphy and painting art in the Jiangnan region. The increasing participation of the urban citizen class in art collection and consumption further stimulated the flourishing of the art market and accelerated the dissemination of cultural capital. Objective: This study analyzes Along the River During the Qingming Festival and Prosperous Suzhou in order to explore the commercialization and marketization of calligraphy and painting during the Ming and Qing dynasties, while revealing their influence on the popularization of cultural capital. Methods: Taking these two artworks as primary research texts, this study employs iconographic analysis and literature review methods to examine representations of the art trade in the Jiangnan region depicted within the paintings. By integrating visual analysis with historical evidence, the research investigates the complex relationship between art and the market and discusses the developmental transformation of calligraphy and painting under the influence of commercialization. Results: The findings indicate that Along the River During the Qingming Festival and Prosperous Suzhou vividly portray the prosperity of Jiangnan society during the Ming and Qing dynasties, reflecting a close connection between visual culture and material culture. The artworks demonstrate how the sacred and elite status traditionally associated with calligraphy and painting gradually weakened under commercial influences, transforming these art forms into cultural products appreciated by both elites and ordinary people. Conclusion: This research deepens the understanding of the art market in the Jiangnan region during the Ming and Qing dynasties and highlights the profound influence of commercialization on artistic forms and the dissemination of cultural capital, thereby providing new perspectives for contemporary studies of art markets and cultural consumption.
Keywords: "Qing Ming Shang He Tu"; "Gu Su Prosperity Tu"; Ming and Qing Dynasty Painting and Calligraphy Art Market; Commercialization